2016
DOI: 10.1210/jc.2016-3285
|View full text |Cite
|
Sign up to set email alerts
|

11-Oxygenated C19 Steroids Are the Predominant Androgens in Polycystic Ovary Syndrome

Abstract: Context:Androgen excess is a defining feature of polycystic ovary syndrome (PCOS), but the exact origin of hyperandrogenemia remains a matter of debate. Recent studies have highlighted the importance of the 11-oxygenated C19 steroid pathway to androgen metabolism in humans. In this study, we analyzed the contribution of 11-oxygenated androgens to androgen excess in women with PCOS.Methods:One hundred fourteen women with PCOS and 49 healthy control subjects underwent measurement of serum androgens by liquid chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
156
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(169 citation statements)
references
References 33 publications
8
156
3
2
Order By: Relevance
“…It is becoming apparent that the steroidogenic repertoire of the adrenal and, perhaps, the theca cell include 11-hydroxyandrostenedione, which is ultimately converted to the potent androgen 11-ketotestosterone [14]. Women with PCOS showed higher serum concentrations of the 11-oxygenated androgens 11β-hy droxyandrostenedione, 11-ketoandrostenedione, 11β-hy droxytestosterone, and 11-ketotestosterone concentrations than control women [15]. …”
Section: A Pathophysiologymentioning
confidence: 99%
“…It is becoming apparent that the steroidogenic repertoire of the adrenal and, perhaps, the theca cell include 11-hydroxyandrostenedione, which is ultimately converted to the potent androgen 11-ketotestosterone [14]. Women with PCOS showed higher serum concentrations of the 11-oxygenated androgens 11β-hy droxyandrostenedione, 11-ketoandrostenedione, 11β-hy droxytestosterone, and 11-ketotestosterone concentrations than control women [15]. …”
Section: A Pathophysiologymentioning
confidence: 99%
“…Importantly, the in vitro androgen receptor-transactivating activity of 11-keto-T and 11-keto-DHT is similar to that of testosterone and DHT [32, 39-41]. The implications of this additional androgen class are wide-ranging: recent studies have shown that they play a key role in androgen excess states, representing the majority of circulating androgens in polycystic ovary syndrome [42]. In addition, 11-oxygenated androgens are found to be increased in CAH due to CYP21A2 deficiency [43-46].…”
Section: Overview Of Adrenal Steroidogenesismentioning
confidence: 99%
“…Recent evidence has shown that the human adrenal cortex would express the enzymes to complete all the steps in the backdoor pathway to DHT [25-27] and that this pathway would contribute to the androgen production in pathological states in which 17OHP accumulates [21, 22, 24]. Moreover, recent studies have demonstrated that the human adrenal cortex also produces a unique set of 11-oxygenated C19 steroids [19, 20, 23]. The first step of the 11-oxygenated androgen pathway is dependent on the adrenal CYP11B1 -catalyzed 11β-hydroxylation of A4 to 11β-hydroxyandrostenedione, which is a major product of adrenal steroidogenesis [19, 20].…”
Section: Functional Zonation Of the Human Adrenal Cortexmentioning
confidence: 99%